Redeeming vision : a Christian guide to looking at and learning from art - Weichbrodt, Elissa Yukiko, 1982- (Grand Rapids, MI. Baker Academic, 2023)
"Premised on the belief that we are all morally formed by images whether we know it or not, this illustrated resource provides a practical guide for Christian viewing, offering tools for closely looking at and interrogating images we encounter in the media and art around us"--
Includes bibliographical references and index.
Keywords: Christianity and art